2005
DOI: 10.1136/bjo.2005.072538
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene in routine glaucoma clinics

Abstract: Bilateral naevus of Ota with choroidal melanoma and diffuse retinal pigmentation in a dark skinned person Naevus of Ota (naevus fusculocoeruleus ophthalmomaxillaris) was described by the Japanese dermatologist, Ota, in 1939 as a dermal melanocytic hamartoma that presents as bluish hyperpigmentation along the ophthalmic, maxillary, and mandibular branches of the trigeminal nerve. It is bilateral in less than 5% cases, occurring frequently in Orientals (0.2%-1%) and darker races and rarely in white people (0.04%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We have not provided feedback about individual physicians' compliance rates in this study; instead, we have started the reporting of monthly hand hygiene adherence rates for each clinical department that takes place at the monthly directors' meeting. As with previous reports, 1,[12][13][14][15] audit and feedback of hand hygiene performance resulted in a significant increase in hand hygiene compliance at the hospital, department, and individual physician levels. However, our methods, based on compliance rate results, were insufficient for hand hygiene improvement initiatives because overall hand hygiene compliance was still low at 18.2%, and only 17.1% of physicians were considered as responders after feedback.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have not provided feedback about individual physicians' compliance rates in this study; instead, we have started the reporting of monthly hand hygiene adherence rates for each clinical department that takes place at the monthly directors' meeting. As with previous reports, 1,[12][13][14][15] audit and feedback of hand hygiene performance resulted in a significant increase in hand hygiene compliance at the hospital, department, and individual physician levels. However, our methods, based on compliance rate results, were insufficient for hand hygiene improvement initiatives because overall hand hygiene compliance was still low at 18.2%, and only 17.1% of physicians were considered as responders after feedback.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies performed in dermatology and glaucoma clinics demonstrated that baseline hand hygiene adherence (attempts/ opportunities) measured by direct observation was 31.4% (174/555) and 18% (44/249), respectively. 13,14 Similarly, direct observation of hand hygiene adherence performed in oncology and gastrointestinal clinic was reported as 11% (74/684) and 21% (164/798) at baseline, respectively. 12 Direct comparison of results obtained in these studies with the results of this study was difficult because the sample sizes were relatively small and were performed only at 1 or 2 clinic or department.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study showed that, using covert observation, handwashing episodes in a glaucoma clinic were only 18%; this increased to 28% when it was remonitored after the preliminary results were presented and distributed by memo. 8 Although this was statistically significant, it was far from the hospital standard. Therefore, we believe that continuous re-inforcement is necessary to improve adherence levels.…”
Section: Hand Hygiene Practices Among Ophthalmologistsmentioning
confidence: 90%
“…Studies have shown that hand hygiene is not always practised by a substantial proportion of ophthalmic healthcare workers [10] and that ophthalmologists can carry a significant microbial load on their hands [11]. This case shows the risk faced by healthcare workers whilst treating infected patients and highlights the importance of the implementation of hygienic measures by both patients (through education on the importance of frequent hand washing and avoiding the sharing of eating utensils/towels) and healthcare workers to reduce the risk of transmission.…”
Section: Discussionmentioning
confidence: 99%